The Ability of Writing Cerpen Procuredly Through Experiential Learning Students of Class IX Junior High School - Musyawir Musyawir; Hamzah Hamzah (IJECA (International Journal of Education and Curriculum Application), 2018)
This study aims to determine the ability of students of class IX SMP Buru 11 in writing short stories in stages through observation of the daily events of experiential learning. This research is a quantitative descriptive study. Namely by describing the profile of student learning outcomes by utilizing ways of interpretation by presenting in the form of descriptions. The results of this study indicate that (1) The ability to write short stories in stages through observation of daily events Experiential Learning in SMP Negeri 11 Buru has been successful, but not yet optimal, (2) aspects of the accuracy of diction which do not meet the maximum value, from the total sample of 26 students who scored 65 and above was 16 people (62%) and 10 students who scored below 65 (38%). This means that the ability of grade IX students of SMP Negeri 11 Buru in writing short stories in stages through observation of daily events (Experiential Learning) is categorized as sufficient.